Respuesta :
Reorder the terms:
5(1 + x) = 4(x + 8)
(1 * 5 + x * 5) = 4(x + 8)
(5 + 5x) = 4(x + 8)
Reorder the terms:
5 + 5x = 4(8 + x)
5 + 5x = (8 * 4 + x * 4)
5 + 5x = (32 + 4x)
Solving
5 + 5x = 32 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
5 + 5x + -4x = 32 + 4x + -4x
Combine like terms: 5x + -4x = 1x
5 + 1x = 32 + 4x + -4x
Combine like terms: 4x + -4x = 0
5 + 1x = 32 + 0
5 + 1x = 32
Add '-5' to each side of the equation.
5 + -5 + 1x = 32 + -5
Combine like terms: 5 + -5 = 0
0 + 1x = 32 + -5
1x = 32 + -5
Combine like terms: 32 + -5 = 27
1x = 27
Divide each side by '1'.
x = 27
Simplifying
x = 27
5(1 + x) = 4(x + 8)
(1 * 5 + x * 5) = 4(x + 8)
(5 + 5x) = 4(x + 8)
Reorder the terms:
5 + 5x = 4(8 + x)
5 + 5x = (8 * 4 + x * 4)
5 + 5x = (32 + 4x)
Solving
5 + 5x = 32 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
5 + 5x + -4x = 32 + 4x + -4x
Combine like terms: 5x + -4x = 1x
5 + 1x = 32 + 4x + -4x
Combine like terms: 4x + -4x = 0
5 + 1x = 32 + 0
5 + 1x = 32
Add '-5' to each side of the equation.
5 + -5 + 1x = 32 + -5
Combine like terms: 5 + -5 = 0
0 + 1x = 32 + -5
1x = 32 + -5
Combine like terms: 32 + -5 = 27
1x = 27
Divide each side by '1'.
x = 27
Simplifying
x = 27
Answer:
x =3
Step-by-step explanation:
5(x + 1) = 4x + 8
Distribute the 5
5x+5 = 4x+8
Subtract 4x from each side
5x-4x+5 = 4x-4x+8
x+5 =8
Subtract 5 from each side
x+5-5 = 8-5
x =3